Apathy in Alzheimer's disease: Contribution to a clinical view on progression of dementia - Stella, Florindo [UNESP]; Andrade, Larissa Pires De [UNESP]; Vital, Thays Martins [UNESP]; Coelho, Flávia Gomes De Melo [UNESP]; Nascimento, Carla Manuela Crispim [UNESP]; Hernández, Salma Stephany Soleman [UNESP] (Associação de Neurologia Cognitiva e do Comportamento, 2010)
In addition to cognitive impairment, apathy is increasingly recognized as an important neuropsychiatric syndrome in Alzheimer's disease (AD).

A apatia tem sido reconhecida como uma importante síndrome na doença de Alzheimer (DA), além do comprometimento cognitivo.
Apatia na doença de Alzheimer: contribuição para uma visão clínica da progressão da demência
Keywords: apathy; Alzheimer's disease; disease progression; apatia; doença de Alzheimer; progressão da doença